IDENTIFIKASI AKUIFER AIR TANAH DI KEC. MANGKUBUMI, KOTA TASIKMALAYA DENGAN METODE GEOLISTRIK - Mardi Wibowo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Along with increase in population and economic growth in Tasikmalaya Residence cause the need of water is increased too. The majority these need take from groundwater resources. Occurrence groundwater resources depends on many factor like landform (landscapes), geology, precipitation, land use, etc. Resistivity geoelectric survey can detect groundwater resources occurrence. This survey can detect geometry and distribution of groundwater reservoir (aquifer). Generally, underground condition of Mangkubumi area consist of 3 layers of lithology i.e. soil layer, sandstone and clayey sandstone and locally there are lens of pebbly sandstones. Sandstones have good potential as aquifer. Sandstone layer is evenlydistributed in Mangkubumi area at depth between 50 cm – 15 m. For shallowgroundwater resources exploitation should be directed at south east and south west part of Mangkubumi area; while for deep groundwater resources exploitation can directed anywhere at depth more than 100 m.